Ethnomedicine of the Kagera Region, north western Tanzania. Part 3: plants used in traditional medicine in Kikuku village, Muleba District - Moshi Mainen J; Otieno Donald F; Weisheit Anke (BMC, 2012)
Abstract Background The Kagera region of north western Tanzania has a rich culture of traditional medicine use and practice. Traditional medicines are the mainstay of healthcare in this region and are known to support the management of many illnesses such as malaria, bacterial infections, epilepsy, gynecological problems and others. However, most of the plants being used have either not been documented or evaluated for safety and efficacy or both. This study, the sixth of an ongoing series, reports on the medicinal plants that are used at Kikuku village, Muleba District. Methodology A semi-structured questionnaire was used to collect information on the common/local names of the plants, parts of the plants used, diseases treated, methods of preparing the herbal remedies, dosage of the remedies administered, frequency and duration of treatment and toxicity of the medicines. A literature review was carried out for information on the ethnomedical uses of the reported plants. Results A total of 49 plant species belonging to 47 genera and 24 plant families were documented. The family Euphorbiaceae and Asteraceae had the highest representation. The plants are used for the treatment of skin conditions (10 plants; 20%), bacterial infections and wounds (14 plants; 28.6%), malaria (14 plants; 28.6%), gastrointestinal disorders (11 plants; 22.4%), gynecological problems including infertility (8 plants; 16.3%), hypertension (5 plants; 10.2%), viral infections (7 plants; 14.3%), chest problems (5 plants; 10.2%), diabetes (3 plants; 6.1%), cancer (2 plants; 4.1%), inflammatory conditions (arthritis, rheumatism), HIV and AIDS, and hernia each treated by 1 plant (3 plants in total; 6.1%). Information obtained from the literature indicate that 25 (51.0%) of the therapeutic claims are supported by laboratory results or have similar claims of ethnomedical use from other countries. Conclusion Herbal remedies comprise an important and effective component of the healthcare system in Kikuku village with plants in the families Euphorbiaceae and Asteraceae comprising an important part of plants used in the indigenous healthcare management in the village. Malaria and bacterial infections dominate the list of diseases that are managed using traditional medicines.